Improving Student Learning Outcomes on Asmaul Husana Material through the Discovery Learning Method at SD Negeri Ulee Tutue - Nurasiah; Safrina (ETNOPEDAGOGI: Jurnal Pendidikan dan Kebudayaan, 2025)
This study aims to improve the learning outcomes of fifth-grade students at SD Negeri Ulee Tutue on the subject of Asmaul Husna through the application of the Discovery Learning method. The research employed classroom action research (CAR) implemented in two cycles. Based on the results, it was concluded that the use of the Discovery Learning method significantly enhanced students’ learning outcomes. The average score increased from 64.5 in the pre-cycle, to 68 in Cycle I, and reached 78 in Cycle II. Similarly, the completeness of student learning improved from 35% in the pre-cycle, to 55% in Cycle I, and finally to 85% in Cycle II. In addition, the method also increased teacher activity in guiding students and summarizing lesson materials. Student activity also improved, as they were more attentive during the learning process, actively asked and answered questions, and engaged more in classroom interactions. These findings indicate that Discovery Learning is effective in enhancing both learning outcomes and classroom engagement in the subject of Asmaul Husna.